Enteropathic Spondyloarthritis: From Diagnosis to Treatment. (15th April 2013) - Peluso, Rosario; Di Minno, Matteo Nicola Dario; Iervolino, Salvatore; Manguso, Francesco; Tramontano, Giuseppina; Ambrosino, Pasquale; Esposito, Carmela; Scalera, Antonella; Castiglione, Fabiana; Scarpa, Raffaele
Abstract : Enteropathic arthritis (EA) is a spondyloarthritis (SpA) which occurs in patients with inflammatory bowel diseases (IBDs) and other gastrointestinal diseases. Diagnosis is generally established on the medical history and physical examination. It was, generally, made according to the European Spondyloarthropathy Study Group (ESSG) criteria. Rheumatic manifestations are the most frequent extraintestinal findings of IBD with a prevalence between 17% and 39%, and IBD is associated, less frequently, with other rheumatic disease such as rheumatoid arthritis, Sjogren syndrome, Takayasu arteritis, and fibromyalgia. Although the pathogenesis of EA has not been plainly clarified, the most popular theory supposes that joint inflammation occurs in genetically predisposed subjects with bacterial gut infections, provided an important evidence for a possible relationship between inflammation of the gut mucosa and arthritis. The management of patients with EA requires an active cooperation between the gastroenterologist and rheumatologist.